DEVELOPING ENGLISH SPEAKING MATERIALS FOR THE RECEPTIONIST OF GALUH HOTEL - Deni Prakasa Karuniawan; Rr. Hasti Robiasih (Universitas Sarjanawiyata Tamansiswa, 2018)
The objectives of this study are: (1) to describe how English speaking materials are developed for the receptionist of Galuh Hotel and (2) to find out the coverage of speaking materials for the receptionists. This study is a Research and Development (R & D). The researcher applied Research & Development based on Kemp’s model (1977) namely (1) Research and Information Collecting (needs analysis), (2) Planning (stating goals, topics, general purposes, and objectives), (3) Develop preliminary form of product (listing subject content, selecting teaching/learning activities and evaluation), (4) Main Product Revision (revision). The results show that the speaking materials for receptionist of Galuh Hotel consisted of four units entitled (1) Hi...Good Morning, (2) Let Me Introduce…, (3) Please Forgive Me, (4) Thanks for…. In each unit there were four sections: Snapshot, Come and Speak It up, Language Focus and Get These Questions Answered. The materials covered topic, language function, grammar and vocabulary.